Digital Disruption in South African Television News - Stos, Susan (Television in Africa in the Digital Age, 2021)
The term digital “disruption” conjures up negative connotations, with implications of disturbance, interference or interruption. Certainly, virtually every aspect of life has been affected by digitisation, but it has been pointed out that it is detrimental “only for those who chose to ignore it or try to ﬁght it” (“Digital Disruption: What Is It?” 2016, para 2). One case in point is the American company Kodak. Where it once dominated the ﬁlm and camera market for most of the twentieth century, the company recently ﬁled for bankruptcy. Kodak’s mistake was continually opposing the digitisation of the industry and failing to read the writing on the wall (“Digital Disruption: What Is It?” 2016). Digitisation is as much a reality of life in the newsroom as it is in the boardroom.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Imaginarios y estrategias decoloniales - Ferrera-Balanquet, Raúl Moarquech (Estudios Artísticos, 2018)
Enunciando el delinking de la matriz moderna/ colonial, este artículo imagina un territorio crítico teórico creativo partiendo de la aesthesis decolonial con el fin de dialogar con una serie de hacedores culturales que emplean estrategias creativas decoloniales en proyectos creativos. Un acercamiento a la exposición Haceres Decoloniales (2015) realizada en Bogotá, ofrece la oportunidad de conversar sobre el hacer creativo de Benvenuto Chavajay, Rosa Tisoy Tandoy y Marco Alonso Roa. Los efectos de la colonialidad sonora conllevan a dialogar con la artista maya k´iche Sandra Monterroso y el creador maya yucateco Isaac Carrillo Can. Discursamos sobre el proyecto Espejo Negro (2010) de Pedro Lasch y el mural Las Aguas Sagradas de La Llorona (2004) de la artista xicana Juana Alicia. Terminamos con una interpretación crítica sobre el proyecto Mariposa Memoria Ancestral (2013-2015), y el performance multidisciplinario Whip It Good (2013) de la artista danesa trinitobaguense Jeannette Ehlers. En reliant la déconnexion de la matrice moderne / coloniale, cet article imagine un territoire créatif- théorique-critique à partir de l’aesthésis décoloniale, afin de dialoguer avec une série d’acteurs culturels qui utilisent des stratégies décoloniales créatives dans des projets créatifs. Une approche de l’exposition Haceres Decoloniales (2015) tenue à Bogotá, offre l’occasion de parler du travail créatif de Benvenuto Chavajay, Rosa Tisoy Tandoy et Marco Alonso Roa. Les effets de la colonialité sonore impliquent un dialogue avec l’artiste maya k’iche Sandra Monterroso et le créateur maya yucatècque Isaac Carrillo Can. Nous parlons du projet Espejo Negro (2010) de Pedro Lasch et de la peinture murale Las Aguas Sagradas de La Llorona (2004) de l’artiste chicane Juana Alicia. Nous terminons avec une interprétation critique du projet Mariposa Memoria Ancestral (2013-2015) et la performance pluridisciplinaire Whip It Good (2013) de l’artiste danois né en Trinité-et-Tobago Jeannette Ehlers.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Black Art: Ancestral Legacy : The African Impulse in African-American Art. - Dallas Museum of Art (Dallas Museum of Art, 1990)
For the first time, a major exhibition examines the impact of African culture on black artists, both trained and self-taught, in a stunning range of 157 works which are variously bold, witty, historical, and mysterious. 49 biographical outlines; 320 illustrations, 170 in full color.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé